Palo : knock on wood - Giovannone, Giulia; Antal, Csilla; Baerlocher, Lorenz; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
Palo is a premium wooden eyewear brand tailored to a particular niche of nonconformist people inspired by high quality and innovative products linked to nature. Products manufactured in China are shipped to many countries around the world, with the main focus on the European market. Initially the company expanded without a clear strategy and focus, making use of trade fairs and some existing contacts. They began selling in 21 countries, mainly through sales agents, distributors and by personally contacting retailers. After the initial successes, the expansion of the brand was jeopardized by the lack of financial resources and production delays, as well as internal team conflict. Internal problems were coupled with the increasing competition, as more and more start-ups entered the wooden eyewear market. Palo was losing momentum and its first mover advantage was rapidly disappearing. Action was needed immediately if the company was to survive. After Chris Rasker, the new CEO, took over the entire operations, he was eager to prioritize markets and find the right distribution channel among the wide spectrum of possible combinations.
Originally Published InGiovannone, G., Antal, C., Baerlocher, L., & Hulsink, W. (2014). Palo: Knock on wood. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Palo -- Case studies; Business planning -- Case studies; Strategic planning -- Case studies; Globalization -- Case studies